Disseminated Staphylococcus aureus infection in an adolescent patient following a traditional phlebotomy procedure - Oon, Zhi Sing; Abdul Razak, Ardilla Hanim; Awang, Shukrimi (SPRINGER NATURE, 2023)
Al-Fashdu is a well-known Islamic medicine-based alternative treatment, and it has been widely practiced with the aim of treating certain health issues in various countries. Unfortunately, this therapy can lead to certain complications, including life-threatening infections. We report a case of a 12-year-old male patient who developed a disseminated Staphylococcus aureus infection following Al-Fashdu therapy. He was treated with surgical drainage and intravenous antibiotics. To our knowledge, this is the first report of a disseminated Staphylococcus aureus infection following Al-Fashdu therapy in an adolescent patient.